Klarifikasi Konseptual Ijtihad, Mujtahid, dan Fatwa serta Urgensinya dalam Dinamika Hukum Islam Kontemporer - Rifqi Halim (Dirosah Islamiyah, 2026)
Ijtihad, mujtahid, and fatwa are three fundamental elements in the Islamic legal system that serve to maintain the relevance of sharia amidst ever-evolving social dynamics. This article aims to conceptually examine the meaning of ijtihad, the qualifications of mujtahid, and the position of fatwa in Islam, while also explaining the functional relationship between them. This research uses a qualitative approach with library research methods, using data sources in the form of the Quran, hadith, classical texts, and contemporary literature on ushul fiqh and Islamic law. The data are analyzed descriptively and analytically to gain a comprehensive understanding of the role of ijtihad and fatwa in addressing legal issues not explicitly addressed in the texts. The results of the study indicate that ijtihad is the primary mechanism in legal exploration, the mujtahid plays an authoritative role in the process, and the fatwa serves as a legal product that serves as practical guidance for the community. This article emphasizes that the sustainability of Islamic law depends crucially on the integration of these three elements to ensure that sharia remains dynamic, contextual, and grounded in the principles of revelation.